Distribution of Cows by Days in Milk (DIM) at First AI and Calving to Conception Interval in Dairy Cows - M Yusuf; A L Toleng; M F Syafar (Media Peternakan, 2012)
The objective of this study was to show the distribution of cows by days in milk (DIM) at first artificial insemination (AI) and the interval from calving to conception. The study was conducted in 47 commercial dairy herds in Enrekang Regency from May to October 2011. Of 289 animals, 143 of them or 49.5% were dairy Holstein Friesian cows with parities one to seven; mean (±SD) 2.05±1.50. The cows were classified into six groups based on DIM at first AI; within 40 d postpartum, between 41 and 85 d, 86 and 115 d, 116 and 150 d, 151 and 210 d, and 211 days or more. The cows were classified into five groups based on the interval from calving to conception; within 85 d postpartum, 86 and 115 d, 116 and 150 d, 151 and 210 d, and 211 days or more. The results of this study showed that the interval from calving to first AI was 131.6±121.8 d. The percentage of cows inseminated within 85 d after calving was only 56.1%; significantly lower (P < 0.01) than the percentage in the list of fertility management assessment standard. Likewise, cows conceived within 150 d after calving was only 32%. In conclusion, a longer average days in milk (DIM) at first AI in dairy cows was found in the present study, subsequently reduced the possibility of the cows to become pregnant in an optimum time, and reduced the reproductive performance of the herds.